The outcome of singleton breech delivery - Yaakob, Che Anuar Che (1995)
Breech presentations and breech births are reported to have increased morbidity and mortality when compared to cephalic presentation Hall and Kohl 1956 stated that the type of breech influenced the perinatal morbidity and the risk of cord prolapse with non-frank breech increased by six folds There was also increased intrapartum and neonatal deaths with non-frank breech presentation . The concept of elective caesarean section in all primigravida term frank breech needed in some to be reviewed Caesarean section is absolutely necessary if the biparietal diameter exceeds 10 centimetres with hyperextended head and where inadequacy of pelvis is suspected However caesarean delivery is not associated with a lower risk of either perinatal mortality or intraventricular haemorrhage in very low birth weight infants weighing less than 1500g Denise M Martin et al 1983 It was noted that no significant differences found in the incidence of lower Apgar scores traumatic birth injury or requirement for neonatal resuscitation between those infants delivered via caesarean section and vaginal delivery .